Hungary : Selected Issues. (IMF Staff Country Reports; Country Report, 1999)
This Selected Issues paper on Hungary presents an empirical analysis of the leading indicators for inflation and models the determinants of inflation. It summarizes current knowledge about the behavior of inflation and thus underpins the subsequent discussion of possible changes to the current nominal anchor framework. The paper analyzes the growth potential and fiscal issues affecting that potential, and the external constraint. The paper suggests that some relatively stable econometric relationships can be found, despite the considerable structural and policy changes that occurred during the 1990s.